PENGARUH VARIASI KOMPOSISI AMPAS TEBU DAN SERBUK GERGAJI PADA PAPAN PARTIKEL TERHADAP KONDUKTIVITAS TERMAL - Fitri Maiwita (Department of Physics – Universitas Negeri Padang UNP, 2014)
Lack of utilization of bagasse and sawdust has been a big problem for the sugar and the wood industry in Indonesia. Bagasse and sawdust is used as fuel only and the rest is thrown away. The content of the bagasse lignocellulosic allows to be used as particle board. Particle board with variations in the composition of bagasse and sawdust had been investigated previously by testing his physical and mechanical properties. However, the thermal conductivity testing has not been done. Therefore, researchers would like to continue this research by testing the thermal conductivity of the particle board with thermal conductivity apparatus,, because it contains silica bagasse. Silica is a ceramic material that is an insulator so it is hoped will be used as a heat isolator. Created by varying the particle board bagasse and sawdust that is 100 % : 0 % , 75 % : 25 % , 50 % : 50 % . The process of manufacture of particle board made ​​with compression heat for 20 minutes with pressure of 160 kg/m2 and temperature of 180 ° C. Based on the results obtained by the value of the thermal conductivity of particle board with a composition ratio of bagasse and sawdust 100 %: 0 is equal to 0.08 W / m ° C, 75 % : 25 % ie 0.11 W / m ° C , and 50 % : 50 % ie 0.14 W / m ° C. The smaller the bagasse composition, the greater is thermal conductivity. From the results obtained, it can be concluded that the particle board as an heat isolator has the lowest thermal conductivity, that is 0.08 W / m ° C with 100 % bagasse composition. Giving sawdust makes thermal conductivity value increases so that the quality of heat isolator decreases. Keywords: Bagasse , Sawdust , Thermal Conductivity , Particle Board